Pengelolaan Sekolah Berbasis Keunggulan Lokal (Studi Kasus di SMK Negeri 8 Surakarta) - WAGIMIN, Wagimin, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Samino, M.M (2015)
Wagimin, School Management Based on Local Excellence (Case Study in SMK Negeri 8 Surakarta), Thesis, Master of Education Management, Graduate Program, University of Muhammadiyah Surakarta. This study has three aims. 1). Planning school-based local advantages. 2). The implementation of school-based management of local excellence. 3). Evaluation and supervision of schools of local excellence. The method used is descriptive method qualitative approach. The study design using case study strategy. The Object of this research is human and natural resources in SMK Negeri 8 Surakarta. Data, data sources in the form of primary data and secondary data are, the Principal, Vice Principal, Teachers, Personnel, Students and certain documents that exist SMK 8 Surakarta. The technique of collecting data through observation, interviews and documentation. Data analysis techniques with interactive model means that researchers collect data directly from those in the environment at SMK Negeri 8 Surakarta. The validity of the data using member checks techniques and triangulation techniques. This reseach has three results of this study is that the SMK 8 Surakarta. 1). The potential ability / strength / uniqueness that no other school in the form of Karawitan (Javaness music art tradition) programme, the art of dance tradition programme, local puppetry art programme and art music programme. This potential is used as a local superior school. 2). Local excellence was developed through empowerment / optimization of the entire school community, curriculum development implementable / herb, school management based performing arts (MANSENIPER). 3). Evaluation of school supervision through the quality control system ISO 9001: 2001, the quality of the result is determined through evaluation of outcomes and processes and systems management oriented to customer satisfaction.